(untitled) (ETIMA, 2021)
Abstract A solid English Language comprehension is a necessity in today’s technology driven world. Furthermore, the significance of the English Language is only amplified by its presence in modern higher education. This paper presents a smartphone and wearable device oriented language learning model which can be used both during and after lectures. The model intents to gradually enrich the students’ English language vocabulary as they proceed further with their lectures. Additional features are designed to help students improve their pronunciation of the newly discovered words. A key point that makes this model efficient is that students can advance their vocabulary and pronunciation skills paralleled with their study subjects. Key words Language learning, Blended Learning, English vocabulary app.